The Concept of Fitrâh In The Qur'ân And The Implications With Children's Education - Sudrajat Sudrajat; Sun Agustine Agustine Prolawati D. (Jurnal Al-Manar, 2021)
Abstract: The concept of fitrȃh as original goodness connotes a passive acceptance of good and right actions and an active and innate tendency to know Allah and submit to Him. Religion functions as a human moral control. Because religion commands humans always to be aware and able to control themselves Q.S al-Rum: 30, Fitrah sees humans as having self-potential. This potential is the power or strength to accept the religion of monotheism. Therefore, the environment and education have a strategic role in developing human nature. A well-educated fitrah will make itself a nation that loves peace, is inclusive and continues to compete (continuous improvement). The implication of nature on children's education aims to develop the potential of students to become human beings who have faith and piety, have a noble character, are healthy, knowledgeable, capable, creative, independent, and become responsible citizens.Abstrak: Konsep fitrȃh sebagai kebaikan asal, tidak hanya berkonotasi penerimaan pasif terhadap yang baik dan benar tindakan, tetapi kecenderungan aktif dan bawaan alami kecenderungan untuk mengenal Allah serta tunduk kepada-Nya. Agama berfungsi sebagai kontrol moral manusia. Sebab agama menyuruh manusia untuk selalu dalam keadaan sadar dan dapat menguasai diri Q.S al-Rum: 30. Fitrâh memandang manusia memiliki potensi diri. Potensi tersebut adalah daya atau kekuatan untuk menerima agama atau Tauhid. Oleh karena itu, lingkungan dan pendidikan memiliki peran strategis dalam mengembangkan fitrȃh manusia. Fitrȃh yang terdidik dengan baik akan menjadikan dirinya sebagai generasi bangsa yang cinta damai, inklusif dan terus bersaing (continous improvement). Implikasi fitrȃh terhadap pendidikan Anak bertujuan mengembangkan potensi peserta didik agar menjadi manusia yang beriman dan bertakwa, berakhlak mulia, sehat, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang bertanggung jawab.